Special season - Lingual revolution and human civilization - episode The beginning of the world - Yaacob, Solehah@Nik Najah Fadilah (2018)
Hundreds of thousands years of the universal, the earth becomes the most important to be visualized as a part of the existence of life. In Paleozoic age was the life of an ever green swamp forest without flowers or birds or noises of modern insects, there also no big land beasts at all, wallowing amphibian and primitive reptiles were the very highest creatures that life so had so far produced. Life is creeping out of the water, an insect like a dragon fly is shown. There were amphibian like gigantic newts and salamanders, and even primitive reptiles in swaps remain. Then the age of reptiles came, it must have flora green in wet season and brown and purple in the dry. The extinction of Pelycosours, Dinosaurs, Brontosaurus, T-rex, Tyrannosaurus and etc. as a result of meteors exploded. Then the world change into the fertile land especially in the centre of the world which was the Arab Peninsular it`s climate resemble India and Africa. However the change of heavy climate into the dry land had enforced some people migrated to other places such as North (Europe), East (Asia), West (Palestine) and South (Afrika).